Ideology and the face of modern science - Šutović, Milojica (Sociološki pregled, 2024)
Science and scientific arguments are being replaced by ideology, which has become an instrument of capitalist greed, profit maximization and technology materialization. A culture is being created that is largely opposed to scientific reasoning and spirituality. Many scientists are getting rich in a manner criticized by science, casting doubt on the entirety of science, especially social sciences. Knowledge is not a priority, but rather the maximization of profits for private investors, and the protection of the priorities of the power elite. Instead of genuine engagement, academic branding and mind control are being practised. This also involves the degradation of academic work. The publishing and scientific industries work against the scientific community. Scientific results depend on the motives of the sponsors. The industrial form of science works against scientific progress. The coupling with capitalism is the modern face of science, presented in the form of ideology, the ruthless onslaught of capital, by the method of enslaving people. The essential question is how we can protect the freedom and creativity of science. The aim of this paper is to highlight the problem and relevance of these issues, connecting science and propaganda through the instrumentalization of pseudoscience, which negates its subject of research, by legitimizing expert knowledge. The analysis relies on classical texts of great minds and the application of indicative sociology.